Cellular phone based biomedical system for health care - Sukanesh, R; Gautham, P; Arunmozhivarman, P T; Rajan, S Palanivel; Vijayprasath, S (2010 IEEE International Conference on Communication Control and Computing Technologies, 2010)
Tele-health is an inter-disciplinary area where the delivery of health, medical information and services over large and small distances is possible by combining electronic information with communication technologies. Deaths from cardiovascular diseases have decreased substantially over the past two decades, largely as a result of advances in acute care and cardiac surgery. These developments have produced a growing population of patients who have survived a Heart attack. These patients need to be continuously monitored so that the initiation of treatment can be given within the crucial golden hour. The available conventional methods of monitoring mostly perform offline analysis and restrict the mobility of these patients within a hospital or room. Hence the aim of this proposed paper is to enhance the Tele-Health system by providing mobility to both the patient and doctor and regain their independence and return to an active work schedule, there by improving the psychological well being. It is achieved by detecting the changes in Heart rate and blood pressure of the patient in advance and sending an alert sms to the doctor through Global System for Mobile(GSM) Modem thereby gaining immediate medical attention and hence reducing the critical level of the patient.